Village Apparatus Performance in “Jotacorubo” Village, Weru District - Tri Gono; Istatin; Sudarwati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to examine the influence of the variables of Leadership, Utilization of Information Technology, Competence, and Communication on the Performance of Village Apparatus. In this study, the author uses a quantitative descriptive method to determine the magnitude and significance of the influence between variables. The research was conducted in the village of "Jotacorubo," Weru District, Sukoharjo Regency, Central Java Province. The population of all village officials in the village of "Jotacorubo," Weru District, totaling 58 people. The sampling technique used in this study is the census technique. The sample size taken was 58 people or respondents. The variables used in this study consist of 2 (two), namely the dependent variable (Y) and the independent variable (X). The dependent variable (Y) is performance, and the independent variable (X) includes leadership, the utilization of information technology, competence, and communication. Based on the research conducted on the village officials in Jotacorubo Village, Weru District, with the independent variables tested being, the utilization of information technology, competence, and communication, all of leadership which affects the performance of the village officials. In this study, the determination coefficient test yielded an Adjusted R Square value of 0.651, which means that the contribution of the independent variables—leadership, the utilization of technology, competence, and communication—towards the performance variable simultaneously is 65.1%, and the remaining 34.9% is attributed to other factors outside this study. Keywords:Leadership, Utilization of Information Technology, Competence, Communication, and Performance of Village Apparatus